USANZ: Time‐trends in use and impact on outcomes of perioperative chemotherapy in patients treated with radical cystectomy for urothelial bladder cancer. (15th October 2013) - Liew, Mun Sem; Azad, Arun; Tafreshi, Ali; Eapen, Renu; Bolton, Damien; Davis, Ian D.; Sengupta, Shomik
Abstract : Objective: To review time‐trends in the use of perioperative chemotherapy and its impact on oncological outcomes in patients with bladder urothelial cancer (UC) at a single tertiary institution. Patients and Methods: Using electronic and paper medical records, 89 patients were identified who underwent radical cystectomy with or without perioperative chemotherapy between 2004 and 2011 at Austin Health in Melbourne, Australia. Patient demographics, clinico‐pathological characteristics and details of recurrence and death were assessed by retrospective chart review. Survival analysis was carried out using the Kaplan Meier method, with the impact of predictors assessed using Cox proportional hazard models. Results: The median (range) age of this cohort was 65 (37–84) years, and 66 (74%) patients were male. Pathologic features included 68 (76%) pure UC, 21 (24%) mixed UC and 84 (94%) high grade tumours. On clinical staging, 63 (71%) patients had muscle‐invasive bladder cancer (cT‐stage ≥T2), of whom 11 (17%) received neoadjuvant chemotherapy, with an increasing trend in use over time. Following radical cystectomy, pT‐stage ≥T3 and/or node positive were identified in 35 (39%) patients, of whom 16 (46%) received adjuvant chemotherapy. In addition, five patients with stage pT2 received adjuvant chemotherapy. Of the total cohort of patients, 31 (35%) suffered recurrences, and 33 died, 27 from urothelial carcinoma. On multivariate analysis, after adjusting for age, pT‐stage and pN‐stage, perioperative chemotherapy was associated with a significantly lower risk of recurrence [relative risk (RR) 0.41, p < 0.05], but not death from cancer or all causes. Conclusions: Perioperative chemotherapy, and in particular neoadjuvant chemotherapy, remains relatively under‐utilised at our institution despite recent increases. The significant reduction in the risk of recurrence following treatment with perioperative chemotherapy with radical cystectomy highlights the importance of multi‐modality treatment in bladder UC. Identifying barriers to more widespread implementation of perioperative chemotherapy is critical for enhancing outcomes in patients with bladder UC.